Relevance of in vitro agar based screens to characterize the anti-fungal activities of bacterial endophyte communities. Issue 1 (December 2016) - Shehata, Hanan; Lyons, Eric; Jordan, Katerina; Raizada, Manish
Abstract Background Endophytes are microbes that inhabit internal plant tissues without causing disease. Plant microbial communities consist of large numbers of endophyte species. Understanding the functions of these endophytes is a major challenge. An important function of some endophytes is to suppress fungal pathogens. Typically, plant associated microbes are screened for anti-fungal activities in vitro using the high-throughput dual culture screen, but it is not clear whether this method correlates with the activities of these microbesin planta . Furthermore, it is not clear whether in vitro screening captures all of the microbes that show this activity inside plants. The objective of this study was to evaluate the relevance of the in vitro dual culture method for screening endophytes with anti-fungal activity. Results In parallel, 190 bacterial endophytes from the corn grass family (Zea ) were screened for suppression of two fungal pathogens (Sclerotinia homoeocarpa andRhizoctonia solani ) using the in vitro dual culture method, andin planta using the model plant, creeping bentgrass. All endophytes that showed anti-fungal activityin planta againstSclerotinia homoeocarpa and Rhizoctonia solani  (3 or 4 strains, respectively, out of 190),  were captured in vitro. The in vitro andin planta screening results strongly correlated (r = 0.81 and r = 0.94 for the two pathogens, respectively). Conclusions Evidence was gained here that the in vitro dual culture method is a relevant method for high throughput screening of plant endophyte communities for anti-fungal activity. In our study, the method captured all of the microbes that suppressed the corresponding pathogensin planta .